How to integrate library data into GoTriple: a collaboration with the Text+Consortium (Libellarium: journal for research in the field of information and related sciences, 2026)
Purpose. This report presents a showcase for the collaboration between a national and a European research data infrastructure and community service. First, the organisational and technical approaches are explained. In the second part, examples for data integration are proposed together with participants. Finally, possible transfer and application of the presented workflow are discussed.Approach/Methodology. Following a joint analysis by the Text+ and GoTriple teams, developing a dedicated MARC 21 connector for SCRE was identified as the optimal strategy for integrating Text+. This enabled the import of SSH publications from the German National Library (DNB) into GoTriple. This decision also potentially facilitates the integration of relevant SSH collections managed by other libraries, as MARC 21 is an important standard for library cataloguing and data exchange.Results. There have been several technical challenges in this integration. First of all, MARC 21 is a complex protocol, not easily processed. In this case, the use of dedicated, opensource software libraries was particularly helpful. In addition, multiple options had to be evaluated and tested before a suitable solution for harvesting DNB in GoTriple, as presented here, was found.Originality/Value. The presented example of GoTriple and one of the Text+ resource providers (German National Library) can serve as a best practice for integrating more library catalogue data into the GoTriple platform. It also provides a model for the essential communication and collaboration workflow needed to estimate the effort required for future data integration into GoTriple at the level of an exemplary national infrastructure.
Keywords: bibliographic data; data discovery; data integration; GoTriple; library catalogue; metadata; OPERAS research infrastructure; social sciences and humanities; Text+